(untitled) (Development Service Industry Management, 2023)
The article examines the issue of building a system of strategic HR engineering of a modern enterprise. The essence of the concept of human resource management is defined. The principles of forming the company’s HR-engineering system, the system of its goals, and the structure of functional subsystems are outlined. The goals, tasks, principles, directions of the strategic HR engineering system at the enterprise are characterized. It is emphasized that the implementation of the strategic HR engineering system is based on a well-founded HR strategy, which, like a business strategy, should take into account changes in both the external environment and within the enterprise, and should be able to predict the conditions of the business environment that may arise during planning period. Approaches to determining the essence of the company’s HR strategy, the task of developing an HR strategy, types and stages of its formation are outlined. It was noted that aspects of building a strategic HR-engineering system on the basis of creating a reliable Digital-HR-strategy and its successful implementation require special attention in the conditions of the modern digital transformation of enterprises. The strategy of any modern enterprise aims to maintain a long-term competitive position on the market. Today, the most important factor in achieving a long-term competitive position is the construction of a strategic HR-engineering system, the implementation of which will make it possible to achieve compliance of the company’s competitive workforce with the conditions of the external and internal environment in the long term, which will allow the company to exist, develop and achieve its goals. The system of strategic HR engineering at the enterprise is based on the conceptual principles of strategic management of the enterprise as a whole. The strategic goals of HR engineering must be aligned not only with the general and functional mission and strategic goals of the enterprise, but also with the competitive position of the enterprise, since personnel is the main source of competitiveness of the enterprise. The implementation of the strategic HR-engineering system is based on a well-founded HR strategy of the enterprise, which we propose to understand as a well-founded long-term course of action of the enterprise regarding the formation of competitive human resources, ensuring their effective formation, development and use, aimed at meeting the needs of employees, achieving the set strategic goals of the enterprise with taking into account its resource capabilities and changes in the external environment. The HR strategy of the enterprise enables the enterprise to assess the strengths and weaknesses of the personnel potential from the point of view of competitive advantages; assess opportunities and threats from the external environment; create a base for the distribution of human resources; determine alternative actions or combinations of actions regarding the formation and effective use of personnel potential. The digital transformation of the HR engineering system involves the transformation of all HR processes from manual documentation and execution to automated ones, and the transfer of the most time-consuming procedures and operations to the digital environment. The Digital-HR-Strategy is a roadmap that guides the digital transformation of HR-engineering business processes, the overall goal of which is to digitize, automate and thereby improve key strategic HR-engineering functions and processes. The system of strategic HR-engineering allows enterprises to attract the necessary human resources, coordinate production activities and services with consumer demand, respond to the challenges of the external environment and make timely flexible adjustments and changes in the enterprise to achieve a clear competitive advantage.